PENATALAKSANAAN FISIOTERAPI PADA PASIEN SPRAIN ANKLE DEXTRA DENGAN ULTRASOUND DAN TERAPI LATIHAN - Arga Wicaksono; Kuswardani, Kuswardani (Journal of Innovation Research and Knowledge, 2025)
Background: Ankle sprain injuries are injuries that often occur during physical exercise. Ankle sprain injuries can cause damage to the surrounding ligament structures. The occurrence of ankle sprain injuries that often occur can lead to worsening and are known as chronic ankle instability (CAI). Methods: This Scientific Paper is a case study, raising patient cases and collecting data through the physiotherapy process. The modalities provided are Ultrasound, and Exercise Therapy. Results: After four interventions with Ultrasound and Exercise Therapy on this Right Ankle Sprain. The results obtained were a decrease in pain in the ankle, a decrease in spasm, an increase in the range of joint motion, and an increase in muscle strength. Conclusion: Ultrasound, and Exercise Therapy given to patients can help reduce pain, reduce spasm in the Gastrocnemius, increase muscle strength in the ankle, range of motion of the right ankle joint, and the patient's functional activity ability